In Vivo Compositional Changes in the Articular Cartilage of the Patellofemoral Joint Following Anterior Cruciate Ligament Reconstruction. Issue 7 (13th April 2022) - Boling, Michelle C.; Dupell, Matthew; Pfeiffer, Steven J.; Wallace, Kyle; Lalush, David; Spang, Jeffrey T.; Nissman, Daniel; Pietrosimone, Brian
Abstract : Objective: To compare T1ρ relaxation times of the medial and lateral regions of the patella and femoral trochlea at 6 and 12 months following anterior cruciate ligament reconstruction (ACLR) on the ACLR and contralateral extremity. Greater T1ρ relaxation times are associated with a lower proteoglycan density of articular cartilage. Methods: This study involved 20 individuals (11 males, 9 females; mean ± SD age 22 ± 3.9 years, weight 76.11 ± 13.48 kg, and height 178.32 ± 12.32 cm) who underwent a previous unilateral ACLR using a patellar tendon autograft. Magnetic resonance images from both extremities were acquired at 6 and 12 months post‐ACLR. Voxel by voxel T1ρ relaxation times were calculated using a 5‐image sequence. The medial and lateral regions of the femoral trochlea and patellar articular cartilage were manually segmented on both extremities. Separate extremity (ACLR and contralateral extremity) by time (6 months and 12 months) analysis of variance tests were performed for each region ( P  < 0.05). Results: For the medial patella and lateral trochlea, T1ρ relaxation times increased in both extremities between 6 and 12 months post‐ACLR (medial patella P  = 0.012; lateral trochlea P  = 0.043). For the lateral patella, T1ρ relaxation times were significantly greater on the contralateral extremity compared to the ACLR extremity ( P  = 0.001). The T1ρ relaxation times of the medial trochlea on the ACLR extremity were significantly greater at 6 ( P  = 0.005) and 12 months ( P  < 0.001) compared to the contralateral extremity. T1ρ relaxation times of the medial trochlea significantly increased from 6 to 12 months on the ACLR extremity ( P  = 0.003). Conclusion: Changes in T1ρ relaxation times occur within the first 12 months following ACLR in specific regions of the patellofemoral joint on the ACLR and contralateral extremity.